Shareholder wealth creation in response to announcements of acquisitions of unlisted firms: Evidence from Spain - Farinós, José E. (2012)
We investigate shareholder value creation of Spanish listed firms in response to announcements of acquisitions of unlisted companies and compare this experience to the purchase of listed firms over the period 1991–2006. Similar to foreign markets, acquirers of listed targets earn insignificant average abnormal returns, whereas acquirers of unlisted targets gain significant positive average abnormal returns. When we relate these results to company and transaction characteristics our findings diverge from those reported in the literature for other foreign markets, as our evidence suggests that the listing status effect is mainly associated with the fact that unlisted firms tend to be smaller and lesser–known firms, and thus suffer from a lack of competition in the market for corporate control. Consequently, the payment of lower premiums and the possibility of diversifying shareholders’ portfolios lead to unlisted firm acquisitions being viewed as value–orientated transactions.